2007
DOI: 10.1002/chem.200700289
|View full text |Cite
|
Sign up to set email alerts
|

Can [M(H)2(H2)(PXP)] Pincer Complexes (M=Fe, Ru, Os; X=N, O, S) Serve as Catalyst Lead Structures for NH3 Synthesis from N2 and H2?

Abstract: Eine Doppelbegabung: Der Russe Alexander Borodin war ein wegweisender Komponist und wichtiger Chemiker seiner Zeit. Dass er als der Entdecker der Aldol‐Reaktion angesehen werden muss, ist heute weitgehend unbekannt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 67 publications
1
33
1
1
Order By: Relevance
“…[63] Reversible exchange of the H 2 ligand for N 2 was observed and was subsequently used as a starting point for a theoretical investigation into the applicability of 25 as a catalyst for N 2 reduction. [64] More notably, rapid H-D exchange was noted when complex 25 was treated with [D 8 ]toluene, with a high preference for exchange at the sp 2 carbon atoms. Initial deuteration occurred at the para-CH as well as the CH 2 spacer groups, with subsequent additional scrambling into the hydride and tert-butyl fragments.…”
Section: Other Chemistry With Rutheniummentioning
confidence: 98%
“…[63] Reversible exchange of the H 2 ligand for N 2 was observed and was subsequently used as a starting point for a theoretical investigation into the applicability of 25 as a catalyst for N 2 reduction. [64] More notably, rapid H-D exchange was noted when complex 25 was treated with [D 8 ]toluene, with a high preference for exchange at the sp 2 carbon atoms. Initial deuteration occurred at the para-CH as well as the CH 2 spacer groups, with subsequent additional scrambling into the hydride and tert-butyl fragments.…”
Section: Other Chemistry With Rutheniummentioning
confidence: 98%
“…The thermodynamically much more stable end‐on complex 1 will form; however, according to calculations by our group it seems impossible to transfer a metal‐bound hydride centre to the terminal N atom of the N 2 molecule. Instead, we have repeatedly shown that the transfer of the hydride onto the N atom of a side‐on coordinating N 2 molecule like 2 is possible, even with low barriers …”
Section: Concepts For the Development Of Mononuclear Catalystsmentioning
confidence: 99%
“…The fact that the associated local minima and transition states for the cycle shown in Scheme were located in a DFT study by our group for ruthenium pincer model complex [Ru(POP)(H) 2 (N 2 )] (POP=2,5‐bis(dimethylphosphanylmethyl)furan) show the reaction to be possible in principal, and we have also subjected other though related ruthenium pincer complexes to such calculations, which have confirmed the general applicability of this approach and also its limitations. A multitude of single‐hydrogen transfer steps in such a mechanism suffer from unreasonable high activation barriers, which define the challenge of this approach.…”
Section: Concepts For the Development Of Mononuclear Catalystsmentioning
confidence: 99%
See 2 more Smart Citations